Evaluation of the most popular accommodation booking portals with regard to consumer and academic usability - Janiak, Małgorzata; Kozłowska-Adamczak, Monika (Turyzm/Tourism, 2018)
The hospitality industry is classified as the most fundamental tourism service. As far as the dynamic development of the internet and its constantly growing number of its users are concerned, it seems natural for tourism managers and hoteliers to reach for this particular medium to present their offers and to sell them. Nowadays, the most significant issue for the entire hospitality industry is the broad scope of the global and international booking portals which are the contemporary distribution channels for tourism products and services worldwide. The aim of the following article is to assess the usability and functionality of four booking portals acclaimed on the Polish market (booking.com, hrs.com, hotels.com and hotel.info) with regard to the consumer’s (tourist’s) point of view and an evaluation of the suitability of this particular source of data for academic research through applying this method to hotels located in five Polish metropolises (Warsaw, Kraków, Łódź, Wrocław and Poznań).